Work stress dan turnover intention pada karyawan milennial: Peran mediasi supervisor support: Work stress and turnover intention in millennial employees: The mediating role of supervisor support - Yuniasanti, Reny; Sandiasih, Komang Mahadewi; Anggraeni, Dewi Soerna; Prahara, Sowanya Ardi; Hamzah, Hazalizah Binti (Persona:Jurnal Psikologi Indonesia, 2023)
In an era of dynamic work, millennials face unique challenges related to job stress that can impact their intention to leave their job, known as turnover intention. This scientific article explores the relationship between work stress and turnover intentions in the millennial generation, focusing on the mediating role of supervisor support to reexamine whether superiors are one of the determinants of millennial employee turnover intentions. This study used a non-probability sampling method with a purposive sampling technique. The subjects of research were millennial generation employees, with at least 3 months of work. Respondents came from Malaysia (64 people) and Indonesia (152 people), with a total of 216 respondents. The instruments used were the Turnover Intention Scale, General Work Stress, and Supervisor Support which have been tested. The research results show: 1). a quite strong and significant relationship between work stress and turnover intention; 2). supervisor support is not significant on turnover intentions; and 3). The effect of work stress on turnover intention with supervisor support as moderate is not significant. The novelty of the results of this research is that it is very inspiring information for management policies for millennial employees who want to stop working by overcoming sources of work stress and fostering a collegial nature with co-workers. Research implications are discussed